The Need for Legal Intervention in Addressing the Impact of Noise Pollution on Reproductive Health in Nigeria - Uzoma, Vivian Ijeoma (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2024)
Noise pollution, an escalating environmental issue, significantly impacts human health and performance. Urbanization and industrialization contribute to pervasive noise from traffic, machinery, and social activities. Noise, defined as unwanted or harmful sound, varies in its effects based on individual sensitivity and environmental context. Sounds exceeding 80dB are particularly disruptive. Noise pollution originates from natural sources, such as insects and weather, and manmade activities, including industrial operations and urban traffic. In Nigeria, inadequate urban planning and unreliable electricity supply, leading to widespread use of noisy generators, exacerbate the problem. Social and religious events further contribute to environmental noise, affecting urban dwellers' wellbeing. The consequences are extensive, impacting physiological, behavioural, cardiovascular, and mental health, leading to hearing loss, sleep disturbances, reduced concentration, and heightened stress. Vulnerable populations like children and the elderly are particularly affected. Wildlife and reproductive health are also adversely influenced, with noise linked to reduced fertility and adverse pregnancy outcomes. The National Environmental Standards and Regulations Enforcement Agency (NESREA) Act addresses noise pollution through standards and regulations, but enforcement is hindered by political interference and inadequate training. This article recommends that strengthening enforcement mechanisms and integrating noise pollution considerations into health policies are crucial for improving public health and environmental quality in Nigeria. Keywords: Noise, Noise Pollution, Environmental law, Environmental Agencies, Reproductive Health.